Theoretical Issues of Analysis and Evaluation of the Activity of Commercial Banks in Uzbekistan - Abdumutalova Gulrukh Shuhratjon's daughter (Research Parks Publishing LLC, 2023)
This article discusses theoretical issues of analysis and assessment of the activity of commercial banks in Uzbekistan. In the article, the author revealed the level of research and analytical methodology of this topic.